Muharebe şartlarında ruh hâlleri - (:unkn) unknown (My University, 2012)
Bir askerin muharebe etme kabiliyeti duygusal durumuna yakından bağlıdır. Muharipten beklenen; düşmanı, tam bir profesyonellik içinde, ne sevimli bir insan ne de nefrete şâyan bir kötülük timsâli addetmeden sadece imha etmesidir. Korku, önüne geçilmesi gereken doğal bir histir. Bir toplumun geleneksel dünya görüşü, askerinin muharebe psikolojisini belirlemede önemli yer tutar. İyi eğitim dayanıklı ve kararlı bir ruhsal durum geliştirir. Savaş suçları esasen bozuk kişilik yapısından kaynaklanır. Harp psikozu, esasen Vietnam Harbinden bu yana tanınır bir kavram olmuştur.

A soldier s ability to fight a battle is deeply related to his emotional state. In battle, one is expected to merely destroy the enemy in a thoroug- hly professional manner, taking him neither as a sympathetic human be- ing nor a hated evil being. Fear is a natural feeling which must be subdu- ed. Traditional worldview of a given society is important in determining the battle psychology of the soldiers. Good training develops perseveran- ce and stable emotional structure. War crimes are essentially caused by disordered personality structure. War psychosis constitutes a concept which comes to recognition basically since the Vietnam War.
Emotional states under battle conditions
Keywords: Tarih